The prevalence of peg-shaped and missing lateral incisors with maxillary impacted canines - Simić, Sanja M; Pavlović, Jasna; Nikolić, Predrag V; Vujačić, Amila; Vukićević, Vladanka; Jovanović, Radovan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Many authors find that impacted maxillary canines is associated with missing and peg-shaped lateral incisor. The aim of this study was to examine the prevalence of peg-shaped and missing lateral incisor in subjects with impacted maxillary canines, and compare the size of maxillary lateral incisor on the side with palatally impacted canines and on the opposite side of the jaw where there is no impaction. Methods. The study included 64 patients with 80 impacted maxillary canines (23 males and 41 females, mean age 16.3). For each maxillary unerupted canine, precisely correct localization and classification into groups was done. We analyzed the morphology of the lateral incisor (normal, atypical) and frequency of missing of lateral maxillary incisors with canine impaction. Then, from the mentioned examinees sample with the maxillary canine teeth, a subgroup was formed. The criteria for selection were those with unilateral palatally impacted canines (33 subjects, 22 females and 11 males, mean age 17.8 years). The linear variables of the maxillary lateral incisor were measured by using digital measurements tools. The t-test was used to test the differences between the groups. Results. Normal morphology of the lateral incisors was found in 72% of the subjects with the impacted canines, 11.2% of the subjects had the peg-shaped lateral incisors, 6% had a bilateral and 4% had unilateral deficiency of lateral incisors. In the subgroup of the patients with unilateral palatal impaction, the middle value of the length of the lateral incisors was 1.9 mm shorter and the middle value of the width of the lateral incisors was smaller by 0.9 mm when comparing to the control group. Conclusion. The frequency of the deficiency of lateral incisors was statistically significantly higher in the group with palatal canine impaction. The maxillary lateral incisors on the side with palatally impacted canines were smaller than those on the side where there was no impaction.